Hormone Molecular Biology and Clinical Investigation (De Gruyter, 2010)
Hormone Molecular Biology and Clinical Investigation is dedicated to the provision of data on molecular aspects of hormones in physiology and pathophysiology. The journal covers the treatment of diseases, such as endocrine cancers, renal and lymphoid carcinoma, hypertension, cardiovascular systems, osteoporosis, hormone deficiency in menopause and andropause, obesity, diabetes, brain and related diseases.